2008
DOI: 10.2174/138920108784567335
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Fungal Ribotoxins

Abstract: Ribotoxins constitute a family of toxic extracellular fungal RNases that exert a highly specific activity on a conserved region of the larger molecule of rRNA, known as the sarcin-ricin loop. This cleavage of a single phosphodiester bond inactivates the ribosome and leads to protein synthesis inhibition and cell death. In addition to this ribonucleolytic activity, ribotoxins can cross lipid membranes in the absence of any known protein receptor. This ability is due to their capacity to interact with acid phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 106 publications
(203 reference statements)
0
14
0
Order By: Relevance
“…Much later, more systematic analysis of fungal genomes revealed that ribotoxins were a more widespread group of proteins within the filamentous fungi than had been previously believed (Lin et al, 1995;Martínez-Ruiz et al, 1999b;Varga and Samson, 2008). All this exhaustive work dealing with the characterization of their mechanism of action at the molecular level has not only helped to understand the basis of their antitumoral action (Lacadena et al, 2007) but also has established the principles to transform some of them into engineered chimeras with potential therapeutic uses (Carreras-Sangrà et al, 2008, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Much later, more systematic analysis of fungal genomes revealed that ribotoxins were a more widespread group of proteins within the filamentous fungi than had been previously believed (Lin et al, 1995;Martínez-Ruiz et al, 1999b;Varga and Samson, 2008). All this exhaustive work dealing with the characterization of their mechanism of action at the molecular level has not only helped to understand the basis of their antitumoral action (Lacadena et al, 2007) but also has established the principles to transform some of them into engineered chimeras with potential therapeutic uses (Carreras-Sangrà et al, 2008, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Because of toxin complexity and reagent loyalty, rarely did individual researchers use more than one toxin, so direct toxin-to-toxin comparisons were seldom undertaken. Even to this day, these three toxins remain among the top choices for immunotoxin development; although, other plant toxins and fungal toxins are also used to make immunotoxins [53,54]. So what were the features that characterize toxin utility?…”
Section: Toxin Candidatesmentioning
confidence: 99%
“…Many toxin warheads have been investigated for potential development as immunotoxin-based therapeutics including: ricin, diphtheria toxin, pseudomonas exotoxin A, gelonin, bouganin, saponin and various mutants of each (Alewine et al ., 2015; Antignani and Fitzgerald, 2013; Carreras-Sangrà et al ., 2008). A number of these immunotoxins have been tested in clinical trials, particularly PE38 (a truncated pseudomonas exotoxin A variant), gelonin and ricin (Borthakur et al ., 2013; Hassan et al ., 2013, 2014; Kreitman et al ., 2000, 2009; Schnell et al ., 2003; Schindler et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They have not, however, been so frequently employed as bacterial toxins in the development of therapeutic immunotoxins, and so far only preliminary characterisation has been reported (Better et al ., 1992; Goyal and Batra, 2000; Rathore et al ., 1997; Wawrzynczak et al ., 1991). Most recently, a colon cancer-specific immunotoxin based on α-sarcin has been described (Carreras-Sangrà et al ., 2008) that exhibited highly specific antitumour activity in mice harbouring colon tumour xenografts (Tomé-Amat et al ., 2015b). These results support the potential clinical application of ribotoxin-based immunotoxins, and particularly those based on α-sarcin.…”
Section: Introductionmentioning
confidence: 99%